Biodiesel synthesis from swine manure. (December 2020) - Kim, Minyoung; Jung, Sungyup; Lee, Dong-Jun; Lin, Kun-Yi Andrew; Jeon, Young Jae; Rinklebe, Jörg; Klinghoffer, Naomi B.; Kwon, Eilhann E.
Graphical abstract: Highlights: Agricultural waste, sustainable swine manure (SM) was converted into biodiesel (BD). Non-catalytic transesterification of SM resulted in 95 wt% of BD yield. Annual BD production from SM released from two countries were estimated. Abstract: This study demonstrates that the biodiesel (BD) from swine manure (SM) could be a promising way for large scale generation of biofuel. Also, the economic and environmental benefits of SM derived BD were evaluated. Transesterification of lipid contents extracted from the collected SM had low BD yield (14.2 wt%) using H2 SO4 catalyst due to high acid value and impurities. However, thermo-chemical non-catalytic transesterification with a porous material showed 94.7 wt% yield of BD from the lipid in SM. Considering the current population of swine, the annual production of BD from SM was estimated. The SM derived BD could cover 19.7 and 46.8 wt% of BD currently produced in both Korea and the USA with the economic benefits of up to $96 million and $2.1 billion, respectively. The proposed approach also can save vast arable lands needed to cultivate oil-bearing feedstocks for BD production.